A stepwise microwave synergistic pyrolysis approach to produce sludge-based biochars: Feasibility study simulated by laboratory experiments. (15th July 2020) - Wang, Chaoqian; Wang, Wenlong; Lin, Leteng; Zhang, Fusen; Zhang, Runing; Sun, Jing; Song, Zhanlong; Mao, Yanpeng; Zhao, Xiqiang
Highlights: A stepwise microwave pyrolysis was proposed for sewage sludge to produce biochar. Physicochemical and structural properties of the biochar product were attractive. Heavy metals could be better solidified in the final biochar via vitrification. The proposed process could potentially shorten processing time to save energy. Abstract: A stepwise microwave synergistic pyrolysis (SMSP) approach is proposed as a new way to relieve disposal problems of the sewage sludge. Here the sludge is first pre-pyrolyzed by a conventional heating stage, and then rapidly pyrolyzed by a microwave-induced heating stage without any extra microwave absorbers or blending needed. Under simulated process pyrolysis conditions, the dried sludge, intermediate and final sludge-based biochar samples were prepared in the laboratory. Their chemical composition, microstructure and morphology, and leaching toxicity of heavy metals were carefully characterized and analyzed by various techniques such as proximate and ultimate analysis, X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, Brunauer-Emmett-Teller (BET), and scanning electron microscope equipped with energy-dispersive x-ray spectroscopy (SEM-EDX). Results showed that the pre-pyrolytic biochar can be rapidly heated up to 1100 °C within 5 min under microwave irradiation. The pre-pyrolytic stage increased the carbonization and ash enrichment degree of the sludge which itself acted as a good microwave absorber while achieving a quick temperature rise under microwave irradiation. The ash remaining ratio and the specific surface area of the biochar derived from the SMSP approach (labelled as SBC2) are increased by 6.46% and 16.17% respectively, compared with the conventional biochar sample (SBC1). And SBC2 still had diverse surface functional groups kept after SMSP. The residual ratios of Ni, Cu, Zn, Pb, Cr and Cd in SBC2 was more noticeable than in SBC1 but the leaching ratios quite the contrary. Vitrification is also well proved by the increment of quartz peak detected by XRD tests, and the formation of melted glassy spheres with elemental composition of Si, Ca, Al observed by SEM-EDX. It can favorably increase solidification level and decrease leaching toxicity of heavy metals in the SBC2. The feasibility of this proposed SMSP concept has been positively supported by our experimental results. The properties of the sludge-based biochar produced from the SMSP approach also show great potential to be utilized as precursors to produce various adsorbents.